Antifatigue effect of okara protein hydrolysate supplementation during cycling exercise in men: a pre-post uncontrolled pilot study - Yu-Jou Chien; Jung-Piao Tsao; Chun-Tse Tsai; I-Shiung Cheng; Chin-Lin Hsu (Taylor & Francis Group, 2024)
Background Prolonged exercise usually leads to exercise fatigue, which has a negative short-term impact on exercise performance and metabolic rate; thus, fatigue needs to be resolved. Okara is a protein-rich residue of soy processing. Enzyme hydrolysis is known to increase the content of branched-chain amino acids (BCAAs), which have been reported to confer benefits for exercise. The purpose of this study was to investigate the antifatigue effect of okara protein hydrolysate (OPH) on cycling exercise.Methods A total of 16 male participants who habitually exercised (2 times or more per week and without participation in athletic contests) were instructed to receive 11.74 g of OPH once a day. They then completed two intense cycling exercise challenges before and after four weeks of supplementation. Exercise time and blood markers related to fatigue and energy metabolism were measured.Results The results showed that the time to exhaustion significantly increased after the treatment. The levels of lactate during exercise and at the end of exercise were significantly lower after treatment than before. Additionally, postexercise insulin sensitivity was increased after treatment.Conclusions This study showed that OPH supplementation can promote endurance in exercise by decreasing the accumulation of fatigue-related metabolites during exercise and can promote energy recovery by increasing insulin function. These findings suggest that OPH has an antifatigue property.